KONTRIBUSI HASIL TES SELEKSI MASUK PERGURUAN TINGGI TERHADAP INDEKS PRESTASI KUMULATIF MAHASISWA VOKASI BIDANG SOSIAL TERAPAN - suprapto, suprapto; Rahmadian, Reza; Mulyono, Wahyu Dwi (Universitas Negeri Surabaya, 2025)
This study aims to analyze the relationship between college entrance test scores in arts, social, numeric, mathematics, Indonesian, and English with the Cumulative Achievement Index (GPA) of vocational students majoring in applied social studies. Data were obtained from students enrolled in vocational study programs and analyzed using Pearson correlation and multiple linear regression. The results showed that scores in the fields of arts, social, and Indonesian had a significant positive relationship with GPA. The multiple linear regression model revealed that the three variables contributed significantly to the prediction of GPA, whereas the numeric, mathematics and English scores did not have a significant effect. The overall regression model was significant (p < 0.001) with an adjusted R² value of 0.216. These findings indicate that verbal, social, and creative abilities are more relevant as predictors of academic success at the vocational level in applied social studies than numerical and mathematical abilities. The results of this study serve as input for rearranging the content weighting of college entrance tests according to the competency needs of graduates.